Heterochromatin in plant meiosis - Cong Wang; Zhiyu Chen; Gregory P. Copenhaver; Yingxiang Wang (Nucleus, 2024)
Heterochromatin is an organizational property of eukaryotic chromosomes, characterized by extensive DNA and histone modifications, that is associated with the silencing of transposable elements and repetitive sequences. Maintaining heterochromatin is crucial for ensuring genomic integrity and stability during the cell cycle. During meiosis, heterochromatin is important for homologous chromosome synapsis, recombination, and segregation, but our understanding of meiotic heterochromatin formation and condensation is limited. In this review, we focus on the dynamics and features of heterochromatin and how it condenses during meiosis in plants. We also discuss how meiotic heterochromatin influences the interaction and recombination of homologous chromosomes during prophase I.